Net CO2 assimilation of apple leaves after the application of fruit thinning compounds - Matej STOPAR; Franc BATIČ (Acta Agriculturae Slovenica)
Mature 'Jonagold', 'Elstar' and 'Golden Delicious' apple trees on M9 rootstock were sprayed with the most frequently used apple thinning compounds in the years 1995, 1996 and 1997. Net CO2 assimilation rate (A), stomatal conductance (gs) and internal CO2 concentration (ci) of apple leaves were measured a few days after carbaryl (800 ppm), terbacil (50 ppm), NAA (15 ppm), NAAm (50 ppm), BA (50 ppm) and ethephon (300 ppm) application. The strongest A suppression of leaves parallel with gs reduction and enhanced ci was observed with terbacil on all cultivars for all years. Carbaryl, NAA, and BA reduced A on 'Jonagold' and 'Golden Delicious' in 1995 while 'Elstar' trees showed A depression of leaves after NAA application in 1997. NAAm and ethephone had no influence on A, gs or ci on any cultivar.